Access to private equity and real firm activity: Evidence from PIPEs - Brown, James R.; Floros, Ioannis V. (Journal of Corporate Finance, 2012)
We study how access to private equity financing affects real firm activities using a broad panel of publicly traded U.S. firms that raise external equity through private placements (PIPEs) between 1995 and 2008. The public firms relying on PIPEs are generally small, high-tech firms that cannot finance investment internally and likely face severe external financing constraints; PIPEs are by far the most important source of finance for these firms. We show that firms use PIPE inflows to maintain extremely high R&D investment ratios and to build substantial cash reserves. We also use GMM techniques that control for firm-specific effects and the endogeneity of the decision to raise private equity and find that PIPE funding has a substantial impact on corporate investment in cash reserves and R&D, and a smaller but significant impact on investment in non-cash working capital, but little impact on fixed investment or acquisitions. Our estimates indicate that R&D investment initially increases by 0.20–0.25 for each dollar of private equity flowing into the firm, and that PIPE funds initially invested in cash ultimately go to R&D. These findings offer direct evidence that access to private equity finance has an important effect on the key input that drives innovation at the firm- and economy-wide levels.